EFEITO ALELOPÁTICO DE Myrcia vittoriana (MYRTACEAE) - Vasconcelos, Loren Cristina (2020)
Victorian Myrcia is a species of Myrtaceae endemic to the Atlantic Forest, found in sandbank and rainforest formations. A recent study suggested that this species could show allelopathic activity over other species in a vegetable community in Restinga, co